أثر الإهمال الطبي في نشوء الجريمة الطبية - قسم الولادة بالمستشفيات الجزائرية نموذجا: دراسة فقهية قانونية - بوصبيع العايش, وهيبة; شهرة, حبيبة (جامعة الوادي - University of Eloued, 2021)
يهدف هذا البحث إلى بيان مفهوم الإهمال الطبي، وأنواعه، كما يوضح علاقة الإهمال الطبي بالجريمة الطبية في الشريعة الإسلامية والقانون الوضعي، وأثره في إنشائها. كما يسلط الضوء على قضايا تناولها القضاء الجزائري، وقعت في قسم الولادة، وذلك بغية الكشف عن دور الإهمال الطبي في حدوث الجريمة الطبية. ويصل البحث في النهاية إلى جملة من النتائج أهمها: قيام علاقة توليدية بين الإهمال الطبي والجريمة الطبية؛ أينما وُجد الإهمال الطبي وُلدت الجريمة الطبية، ذلك أن إهمال الطبيب يُعد فعلا إجراميا مادام قد ترتب عليه ضرر للمريض، وقد تقرر لدى الفقهاء والقانونيين أن الإهمال الطبي في حد ذاته يعتبر جريمة غير عمدية، والتي هي بدورها نوع من أنواع الجرائم الطبية. كما توصلت الدراسة إلى أن قضية وفاة الحامل وجنينها بولاية الجلفة، وقضية وفاة الجنين في ولاية الوادي؛ تندرجان ضمن دائرة الجرائم الطبية الناشئة عن الإهمال الطبي. This research seeks to exhibit the concept of medical negligence and its types. It also clarifies the relationship between medical negligence and medical crime in Islamic Sharia and positive law and its impact on its emergence. It highlights cases dealt with by the Algerian Judiciary that has happened in the maternity section to reveal the medical negligence's impact on the occurrence of the medical crime. The research reached several results, the most important of which is that there is a positive relationship between medical negligence and medical crime. Whenever medical negligence occurs, the medical crime emerges because a doctor's negligence is a criminal act as long as it has harmed the patient. Jurists and legal scholars have decided that medical negligence is an unintentional crime that is a type of medical crime. The study has achieved that the death of the pregnant woman and her fetus' case in Djelfa and the fetus death case in El-Oued are included under the umbrella of the crimes that emerged from medical negligence.
The Impact of Medical Negligence on the Emergence of Medical Crime - The maternity Section in Algerian Hospitals as a Model- (A Jurisprudential Legal Study)
مقال
Keywords: الإهمال الطبي؛ الجريمة؛ قسم الولادة؛ المستشفيات; medical negligence; crime; maternity section; hospitals